Problematika Penggunaan Google Translate dalam Penerjemah Arab-Indonesia pada Mahasiswa PBA di UIN Datokarama Palu - Akhiryani, Atna; M Hisyam Kabbani; Nur Asmawi, Muhammad (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2024)
This study reveals that the use of Google Translate among students of the Arabic Language Education Study Program (PBA) at UIN Datokarama Palu has become a common practice in the process of translating Arabic-Indonesian texts. Although this tool offers convenience and speed, the results of the study show that Google Translate faces various limitations, especially related to translation accuracy and contextual understanding. The two main problem formulations in this study, namely the use of Google Translate among PBA students and the obstacles faced when using this tool, have been answered through qualitative methods involving observation, interviews, and documentation. Data collected from PBA students of the 2021 intake, as well as interviews with the Head of the Study Program and lecturers, identified that students often experience problems such as inaccurate translation results, the inability of the tool to capture contextual meaning, and difficulty in understanding grammatical structures and the use of appropriate diction. The implications of this study are expected to be a reference for the development of more effective translation teaching strategies in academic environments, especially in the Arabic Language Education Study Program.